Systematic literature study on numeracy literacy activities: How to implement it - Endah Isnaintri; Novaliyosi Novaliyosi (Universitas Sarjanawiyata Tamansiswa, 2024)
This article discusses the significance of numerical literacy in using appropriate models and media in mathematics education. The Systematic Literature Review (SLR) used in this article aims to analyze, identify, review, and interpret research on using models and learning media to improve students' numeracy literacy. This literature review involves three stages based on the PRISMA (Preferred reporting Items for Systematics Review and Meta-Analyses) flow diagram, namely literature screening with 153 documents, the Eligibility stage resulting in 58 relevant documents, and the Qualification stage producing 42 documents meeting the inclusion criteria. The eligible documents were analyzed using thematic analysis, highlighting main themes related to learning models and instructional media in numeracy literacy based on a review of 36 articles. The aftereffects of the examination demonstrate how proper models and learning media can upgrade understudies' numeracy proficiency abilities and assist them with applying numerical ideas in regular daily existence. The implementation of numeracy literacy can be done through case examples, problem-solving, and utilization of digital technology. Effective learning models for improving numeracy literacy include project-based learning, problem-based learning, Contextual Teaching Learning (CTL), Realistic Mathematics Education (RME), game-based learning, and Flipped Classroom. Several learning media can include instructional videos, software, cultural innovations, and numeracy literacy modules. These approaches can help students become more active and engaged in mathematics learning.